Research on skeletal muscle impact injury using a new rat model from a bioimpact machine - Liu, Jun; Liao, Zhikang; Wang, Jingkun; Xiang, Hongyi; Zhu, Xiyan; Che, Xingping; Tang, Yuqian; Xie, Jingru; Mao, Chengyi; Zhao, Hui; Xiong, Yan (Frontiers in Bioengineering and Biotechnology, 2022)
Introduction: Skeletal muscle impact injury occurs frequently during sports, falls, and road traffic accidents. From the reported studies on skeletal muscle injury, it is difficult to determine the injury parameters. Therefore, we developed a new model of gastrocnemius impact injury in rats with a bioimpact machine, with which the experimental operation could be conducted in feasibility from the recorded parameters. Through this novel model, we study the skeletal muscle impact injury mechanisms by combining temporal and spatial variation. Methods: The gastrocnemius of anesthetized rats was injured by a small pneumatic-driven bioimpact machine; the moving speed and impact force were determined, and the whole impact process was captured by a high-speed camera. We observed the general condition of rats and measured the changes in injured calf circumference, evaluating calf injuries using MRI, gait analysis system, and pathology at different times after the injury. Results: The gastrocnemius was injured at an impact speed of 6.63 m/s ± 0.25 m/s and a peak force of 1,556.80 N ± 110.79 N. The gait analysis system showed that the footprint area of the RH limb decreased significantly on the first day and then increased. The calf circumference of the injured limb increased rapidly on the first day post-injury and then decreased in the next few days. MRI showed edema of subcutaneous and gastrocnemius on the first day, and the area of edema decreased over the following days. HE staining showed edema of cells, extensive hyperemia of blood vessels, and infiltration of inflammatory cells on the first day. Cell edema was alleviated day by day, but inflammatory cell infiltration was the most on the third day. TEM showed that the sarcoplasmic reticulum was dilated on the first day, the mitochondrial vacuolation was obvious on the second day, and the glycogen deposition was prominent on the fifth day. Conclusion: In our experiment, we developed a new and effective experimental animal model that was feasible to operate; the injured area of the gastrocnemius began to show “map-like” changes in the light microscope on the third day. Meanwhile, the gastrocnemius showed a trend of “edema-mitochondrial vacuolation-inflammatory cell aggregation” after impact injury.